THE APPLICATION OF THE CONSTRUCTIVIST APPROACH IN ART EDUCATION - Teguh Iman Perdana Surbakti; K.M.S. Muhammad Amin Fauzi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The implementation of a constructivist approach in art education has brought significant changes to the educational landscape, positioning students as active constructors of their own knowledge through direct interaction with learning materials. Constructivism enhances student engagement in the learning process, enabling them to develop a more complex understanding of art through deep exploration and reflection. The exploration of color and form in art is not merely about grasping basic concepts but also about cultivating students' abilities to interpret and respond to these elements subjectively. The application of constructivism provides substantial benefits for students, allowing for personal and meaningful learning experiences while promoting continuous and exploratory learning. Furthermore, the use of color and form in art education serves not only as a learning tool but also as a means to foster students' creativity through their imagination. Research that integrates a constructivist approach with art education offers significant contributions to the development of more effective and student-centered teaching methods. The implications of this research include a deeper understanding of student creativity, the development of more adaptive teaching strategies, and the reinforcement of the teacher's role as an effective learning facilitator. Thus, employing constructivism in art education provides a solid foundation for enhancing the quality of education and fostering student creativity.